Risk Management Practices in Sharia Commercial Banks in the Financing Sector - Munawaroh, Lailatul; Efendi, Bahtiar; Nurhayati, Eni Candra (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
To help the Indonesian economy face increasingly complex risks and problems, Sharia Commercial Banks are very important. Threats and difficulties faced by Sharia Commercial Banks both internally and externally. Risk is the possibility of something happening that may have a positive or negative impact on achieving organizational goals. However, work accidents often occur which result in a Sharia Commercial Bank experiencing losses. Of course, recognizing existing risks can prevent work accidents. For this reason, it is necessary to establish a good system that is comprehensive, planned and structured. This research focuses on how to attract investors to provide financing to Sharia Commercial Banks under the auspices of the OJK. This research uses secondary data collection methods in the context of qualitative descriptive research. In the context of Sharia Commercial Bank financing which is under the supervision of the OJK, the findings of this research provide a comprehensive understanding of relevant and efficient risk management techniques. These findings also provide useful direction for other banks in managing financing funds and fostering investor confidence. Furthermore, solving financing problems is carried out with the 3R idea, namely: rescheduling, reconditioning, restructuring